GE_GERICHTE P/23839/2016 vom 26. September 2017 - GE Cour de justice (2017)
ORDONNANCE PÉNALE ; OPPOSITION(PROCÉDURE) ; CITATION À COMPARAÎTRE ; DÉFAUT(CONTUMACE) ; EXCUSABILITÉ ; PERSONNE PROCHE | CPP.355; CPP.201; CPP.85